The Rise of the Low Cost Model in the Airline Industry : A Study of the Strategies of Southwest, RyanAir and Air Asia - Harsh, Saraogi (2011)
The last decade has seen a major overhaul in the Airline Industry, with the emergence of a new breed of Airlines, the Low Cost Airlines. The trend that started from the United States, with Southwest being the pioneer, slowly and gradually replicated its way through Europe, Asia and the Rest of the World. Today, more than 1 flight in every five worldwide is now operated by a low cost carrier (LCC). The purpose of this paper is to explore the reasons for the growth of the Low Cost Carrier Model in the Airline Industry. Consequently, the paper examines the case of three leading Low Cost Carriers, Southwest in the United States, Ryanair in Europe and Air Asia in South East Asia. The paper begins with a brief introduction of the Airline Industry, followed by the history, background and analysis of the Low Cost Model. Thereafter the paper using principles and ideologies by Michael Porter on competitive advantage, generic strategies and the value chain examines the strategic choices of these three Airlines and the factors that lead to their success. Thereafter a comparative analysis is performed on them and three other leading low cost carriers in both financial and operational terms. And lastly the paper highlights the future challenges for the industry along with the emergence of a new business model and the initiatives taken by these three airlines towards it.